Malaysia’s defense industry: will it has more solid presence and become competitive locally and international market - Othman, Zulbasri; Johari, Mohamad Daud; Yahya, Mohd Nor; Mahomed, Anuar Shah Bali (Science and Engineering Research Support Society, 2019)
The objective of this study is to show the benefits that can be reaped by local industry, especially by small and medium industry players in our country by the creation of national defence industry. There is little emphasis on information pertaining to this industry, especially in regard to small and medium industry groups, in previous studies. This is so perhaps due to difficulty in obtaining secondary data and also national security factor. Researcher is motivated to conduct this study in order to show the role played by local industry players at local and international level. However, there are challenges faced by researcher in collecting data due to factors mentioned earlier and the fact that the needed data are not disclosed to the general public due to security factor and government interests. Hence, this article will discuss concept and opinion pertaining to the potential of small and medium players in defence industry and the strategies that government can use to strengthen this industry; not only in supplying equipment and military facilities to the Armed Forces but also for it to last long and compete in local and international markets.